Respuesta :

so first distribute the 8 out then add everything together:

y-8y-96+4 = -7y-92

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\textbf{Equation:}[/tex]

[tex]\mathbf{y - 8(y + 12) + 4}[/tex]

[tex]\huge\textbf{Solving:}[/tex]

[tex]\mathbf{y - 8(y + 12) + 4}[/tex]
[tex]\huge\textbf{DISTRIBUTE -8 WITHIN the}\\\\\\\huge\textbf{PARENTHESES:}[/tex]

[tex]\mathbf{= y - 8(y) - 8(12) + 4}[/tex]

[tex]\mathbf{= y - 8y - 96 + 4}[/tex]

[tex]\huge\textbf{COMBINE the LIKE TERMS:}[/tex]

[tex]\mathbf{= (y - 8y) + (-96 + 4)}[/tex]

[tex]\mathbf{= y - 8y - 96 + 4}[/tex]

[tex]\huge\textbf{Simplify it!}[/tex]

[tex]\mathbf{ = -7y - 92}[/tex]

[tex]\huge\textbf{Answer:}[/tex]

[tex]\huge\boxed{\mathbf{ -7y - 92}}\huge\checkmark[/tex]

[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]